Pelatihan Pembuatan Gula Semut Sebagai Produk Inovasi Dari Gula Aren di Desa Gelangar - Fatika Agustina; Muhammad Galih Sulendra; Alinda Saputri; Baiq Karni Indrayati; Fitri Wahyu Ramdani; Inda Noviani; Mery Dwi Rahmawati; Muhammad Hizbullah; Nurkhalisa; Nur Izza Latifah; Arben Virgota (Universitas Mataram, 2022)
Gelangsar village is one of the villages producing palm sugar bars of good quality. Palm sugar bars have several disadvantages such as being not durable and impractical. Therefore, the development of product innovation from palm sugar needs to be done. One of the innovations of palm sugar products is ant sugar. Ant sugar is more profitable in terms of practicality, durability, and higher selling value. The purpose of this training is to improve the economy of the village community in Gelangsar. This activity was carried out in 2 stages, notification to the village community, and a series of training events for making ant sugar. In general, this training activity has succeeded in increasing the knowledge and skills of the people of the Gelangsar village in terms of making ant sugar innovation products from palm sugar in the Gelangsar village.